Flexible Electronics: Highly Flexible and Transparent Multilayer MoS2 Transistors with Graphene Electrodes (Small 19/2013). Issue 19 (4th October 2013) - Yoon, Jongwon; Park, Woojin; Bae, Ga‐Yeong; Kim, Yonghun; Jang, Hun Soo; Hyun, Yujun; Lim, Sung Kwan; Kahng, Yung Ho; Hong, Woong‐Ki; Lee, Byoung Hun; Ko, Heung Cho
<x xml:space="preserve">Abstract</x> A highly flexible and transparent transistor based on an exfoliated MoS2 channel and CVD‐grown graphene electrodes is reported by W.‐K. Hong, H. C. Ko, and co‐workers on page 3295. Introducing 2D nanomaterials provides high mechanical flexibility (available bending radius: ± 2.2 mm), optical transmittance (74%), and high current on/off ratio (>104) with an average field effect mobility of ≈4.7 cm2 V−1 s−1, all of which cannot be achieved by other transistors consisting of a MoS2 active channel/metal electrodes or graphene channel/graphene electrodes. In particular, the MoS2/graphene interface has a low Schottky barrier of ≈22 meV, which is comparable to the MoS2/metal interface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>